SOCIO-COGNITIVE CONFLICT AS AN EDUCATIONAL FACTOR IN ACQUIRING NEW KNOWLEDGE AND SOCIAL REPRESENTATIONS: PUBLIC HEALTH STUDY CASE - Jatkauskienė, Birutė; Norkiene, Sigute; Nugaras, Modestas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article is aimed to analyse socio-cognitive conflict as an educational factor in the context of learning and education. For a long time, socio-cognitive conflict had been recognised as a negative factor in a learning or study process. Actually, a positive attitude toward the phenomenon was formed as late as in recent decades – thenceforth, socio-cognitive conflict is claimed to be a positive phenomenon provided that a teacher is able to and knows how to control it, so that to make it a learning incentive, an epistemological source of new knowledge and social representations. The analysis of socio-cognitive conflict and a study of students’ and teachers’ attitudes might help to provide a more comprehensive answer to the following problematic questions: how to perceive and explain the idea of socio-cognitive conflict, its educational importance in the context of learning and education? What are the conditions for a positive solution of socio-cognitive conflict? What is the role of socio-cognitive conflict in a learning or study process? Thus, a goal of the article is to reveal the essence of socio-cognitive conflict and aspects of control thereof in the learning situation from the point of view of students and teachers. The article consists of two parts: the first part addresses a theoretical discourse of the concept of socio-cognitive conflict, and the second part is dedicated to empirical research, i.e., study of an attitude of teachers and students toward the socio-cognitive conflict as a source of new knowledge and social representations.